Abstrak Jurnal Litbang Industri Vol. 13 No. 1 Juni Tahun 2023 - Sofyan Sofyan (Institution for Industrial Research and Standardization of Industry - Padang, 2023)
Abstrak Jurnal Litbang Industri Vol. 13 No. 1 Juni Tahun 2023